A porous ceramic particle with or without a preservative blend did not impair apparent digestibility of macro- and micro-nutrients of postweaned pigs. Issue 3 (9th June 2022) - Davis, Emily M; Liang, Yu; Wallace, Kayla P; Zimmerman, Amanda J; Siebecker, Matthew G; Broadway, Paul Rand; Carroll, Jeffrey A; Ballou, Michael A
Abstract: The objective of this study was to determine the effects of supplementing a commercial porous ceramic clay particle, with or without a blend of preservatives, on the performance and nutrient digestibility of weanling pigs. Fifteen weanling pigs of the Yorkshire, Landrace, and Duroc breeds were blocked by breed and randomly assigned to one of three treatments ( n = 5): (1) Control, non-medicated diet with no additional feed additives (CON); (2) PowerGuard, basal diet with 0.25% of the DM consisting of a ceramic particle mixed into the pelleted feed (PG; MB Nutritional Sciences, Lubbock, TX, 79403); or (3) Power Guard + a blend of preservatives, basal diet with 0.3% of the DM consisting of the ceramic clay and preservatives mixed into the pelleted feed (PG-D). The facility was temperature controlled with an average temperature of 28.5 °C. Pigs were offered ad libitum access to feed and water and were housed individually in elevated crates. Body weights were collected upon enrollment on day 0 and at the end of the observation period on day 18. On day 15, a 72-h total feed and fecal collection period began. Feed and fecal samples were analyzed for DM, CP, Ash, OM, ADF, NDF, zinc, copper, thiamin (vitamin B1), and retinol (vitamin A). Liver samples were collected immediately after harvest and frozen for later mineral analysis. Data were analyzed using Proc Mixed in SAS with dietary group as the main effect and block as the random effect (SAS 9.4, Cary, NC). There were no treatment differences in performance measures including final BW, ADG, or G:F ( P ≥ 0.701). There were no treatment differences in diet nutrient digestibility for DM, CP, Ash, OM, ADF, or NDF ( P ≥ 0.312). Additionally, there were no treatment effects on zinc, copper, or retinol digestibility ( P ≥ .298); however, thiamin inclusion rate was increased for the PG-D treatment, thus leading to an increased digestibility for thiamin ( P = 0.018) in the PG-D treatment. There were no treatment differences in hepatic mineral concentrations ( P ≥ 0.532); however, there was a tendency for pigs fed PG-D to have increased hepatic concentrations of lead and mercury when compared with both PG and CON pigs ( P ≤ 0.066). In summary, supplementation of a commercial ceramic particle with or without a blend of preservatives to weaned pigs did not affect performance or apparent nutrient digestibility.